The seasonal variation in the chemical composition of the kelp species Laminaria digitata, Laminaria hyperborea, Saccharina latissima and Alaria esculenta - Schiener, Peter; Black, Kenneth D.; Stanley, Michele S.; Green, David H. (Journal of applied phycology, 2015)
The seasonal chemical profiling of kelp species has historically either being carried out on only a single species or the data dates back over 60 years. This research highlights a detailed chemical composition profile of the four kelp species Laminaria digitata , Laminaria hyperborea , Saccharina latissima and Alaria esculenta over a 14-month period. These kelp species were selected due to their identified potential for cultivation. They were chemically characterised to identify seasonal variations and predict best harvest times. Components of interest included the carbohydrates cellulose, laminarin, alginate and mannitol as well as proteins, ash, metals, moisture, polyphenolics, total carbon and nitrogen content. The highest yields of lamianrin and mannitol coincided with the lowest yields in ash, protein, moisture and polyphenols. The implications of these observations for use of kelp species as a fermentation substrate are discussed.